2017
DOI: 10.1073/pnas.1613700114
|View full text |Cite
|
Sign up to set email alerts
|

Metaplasticity mechanisms restore plasticity and associativity in an animal model of Alzheimer’s disease

Abstract: Dynamic regulation of plasticity thresholds in a neuronal population is critical for the formation of long-term plasticity and memory and is achieved by mechanisms such as metaplasticity. Metaplasticity tunes the synapses to undergo changes that are necessary prerequisites for memory storage under physiological and pathological conditions. Here we discovered that, in amyloid precursor protein (APP)/presenilin-1 (PS1) mice (age 3-4 mo), a prominent mouse model of Alzheimer's disease (AD), late long-term potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 45 publications
4
34
0
Order By: Relevance
“…Our findings also support earlier work performed in young (6-to 8-week-old) 3xTg mice showing a larger increase than wt mice in RyR-evoked calcium release in response to synaptic stimulation (Chakroborty et al, 2009). In addition, a study in another AD model (APP/PS1) demonstrated that RyR priming reestablishes plasticity (Li et al, 2017). AD mouse models that harbor PS1 mutation release more calcium ions from intracellular stores in response to synaptic stimulation (Cheung et al, 2008;Chakroborty et al, 2009;Chakroborty and Stutzmann, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also support earlier work performed in young (6-to 8-week-old) 3xTg mice showing a larger increase than wt mice in RyR-evoked calcium release in response to synaptic stimulation (Chakroborty et al, 2009). In addition, a study in another AD model (APP/PS1) demonstrated that RyR priming reestablishes plasticity (Li et al, 2017). AD mouse models that harbor PS1 mutation release more calcium ions from intracellular stores in response to synaptic stimulation (Cheung et al, 2008;Chakroborty et al, 2009;Chakroborty and Stutzmann, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, tagging of PKMζ from a strongly tetanized input to a weakly tetanized input is critical for the expression of STC in CA1 pyramidal neurons (31). In addition, we have recently reported that metaplastic activation of PKMζ can rescue the plasticity and associativity that is degraded under neurodegenerative conditions (41).…”
Section: Discussionmentioning
confidence: 96%
“…To rule-out a possible relation of these results with an Sfrp1 developmental function, we sought to interfere with Sfrp1 activity using a neutralizing mAb, given that systemically administered antibodies have been shown to successfully enter and bind to the brain parenchyma 7 . Among the generated mAbs, clone 10.5.6 secreted an IgG1 with Sfrp1 neutralizing activity ( In a second set of experiments we treated animals with the same protocol but for three additional months and then tested whether SFRP1 neutralization would rescue synaptic plasticity deficits already documented for the APP;PS1 mice used in this study 40 . Taken together these data indicate that antibody-mediated neutralization of SFRP1 activity is sufficient to counteract morphological and functional traits of AD.…”
Section: Antibody-mediated Neutralization Of Sfrp1 Activity Counteracmentioning
confidence: 99%